2010
DOI: 10.1369/jhc.2010.956201
|View full text |Cite
|
Sign up to set email alerts
|

Are Human and Mouse Satellite Cells Really the Same?

Abstract: S U M M A R Y Satellite cells are quiescent cells located under the basal lamina of skeletal muscle fibers that contribute to muscle growth, maintenance, repair, and regeneration. Mouse satellite cells have been shown to be muscle stem cells that are able to regenerate muscle fibers and self-renew. As human skeletal muscle is also able to regenerate following injury, we assume that the human satellite cell is, like its murine equivalent, a muscle stem cell. In this review, we compare human and mouse satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 225 publications
(301 reference statements)
1
86
0
1
Order By: Relevance
“…The proliferative ability and temporal expression of mRNA by satellite cells seems to be dependent on the host and the muscle from which they are collected (Powell et al, 2014). Additional levels of heterogeneity are known to exist between satellite cells populations, as well as different extracellular matrix protein compositions, growth kinetics, myoblast fusion capacities, transcription factor profiles, motility kinetics and migratory properties (Biressi and Rando, 2010;Boldrin et al, 2010;Li et al, 2011;Li and Johnson, 2013). There are increasing evidence through gene expression profiling and cell-surface marker analysis that satellite cells are a heterogeneous population (Motohashi and Asakura, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative ability and temporal expression of mRNA by satellite cells seems to be dependent on the host and the muscle from which they are collected (Powell et al, 2014). Additional levels of heterogeneity are known to exist between satellite cells populations, as well as different extracellular matrix protein compositions, growth kinetics, myoblast fusion capacities, transcription factor profiles, motility kinetics and migratory properties (Biressi and Rando, 2010;Boldrin et al, 2010;Li et al, 2011;Li and Johnson, 2013). There are increasing evidence through gene expression profiling and cell-surface marker analysis that satellite cells are a heterogeneous population (Motohashi and Asakura, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This helps to enrich the myoblast fraction as myoblasts show a higher affinity for collagen IV/laminin-coated surfaces than for collagen I/fibronectin-coated surfaces, the latter is preferred by fibroblasts (Kuhl et al, 1986). NCAM was the first marker used to identify human muscle satellite cells, and this marker is expressed in satellite cells, myoblasts, myotubes and muscle fibers during development (Boldrin et al, 2010). This marker is expressed in proliferating human and rat muscle cells, but is not a reliable marker in mice muscle cells; mice muscle cells express NCAM only when they have become committed to differentiation (Capkovic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, differences are also observed between primary cell model systems from different species. The neural cell adhesion marker (NCAM) is expressed in proliferating human and rat cells (Boldrin et al, 2010), but not in mice muscle cells (Capkovic et al, 2008). Cattle are evolutionary closer to humans than rodents, and the entire bovine genome is fully sequenced in order to provide an important supplement for human medical research (Tellam et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most reliable markers of human satellite cells are PAX7 and CD56 (Boldrin et al 2010), and MyoD expression in satellite cells has been previously reported to depend on myogenic differentiation (Bareja et al 2014). Myogenic differentiation was induced by replacing the growth medium with DMEM/Ham's F10 mixture supplemented with 5% horse serum and 1% penicillin-streptomycin (Asakura et al 2002).…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…Muscle satellite cells are typical muscle stem cells that exhibit self-renewal and myogenic differentiation capacities (Judson et al 2013;Gigliotti et al 2016) and are characterized by expression of cluster of differentiation 56 (CD56) in humans (Boldrin et al 2010). These generally quiescent cells are located between the basal lamina and sarcolemma of the skeletal muscle fibers (Zammit et al 2006).…”
Section: Introductionmentioning
confidence: 99%